FUNDAMENTALS OF INVESTMENT ENVIRONMENT IN THE PROCESS OF DIGITAL TRANSFORMATION OF THE ECONOMY - Dilorom Qosimova; Abdujamil Ko‘chimov (Journals Park Publishing, 2022)
The article is devoted to the theoretical substantiation of the problems of improving the investment policy of recipient countries in the conditions of digitalization of economic processes and determining the strategic priorities of investment policy in the digital economy.